Arabidopsis flower specific defense gene expression patterns affect resistance to pathogens - Ederli, Luisa; Dawe, Adam; Pasqualini, Stefania; Quaglia, Mara; Xiong, Liming; Gehring, Chris (Frontiers in Plant Science, 2015)
We investigated whether the Arabidopsis flower evolved protective measures to increase reproductive success. Firstly, analyses of available transcriptome data show that the most highly expressed transcripts in the closed sepal (stage 12) are enriched in genes with roles in responses to chemical stimuli and cellular metabolic processes. At stage 15, there is enrichment in transcripts with a role in responses to biotic stimuli. Comparative analyses between the sepal and petal in the open flower mark an over-representation of transcripts with a role in responses to stress and catalytic activity. Secondly, the content of the biotic defense-associated phytohormone salicylic acid (SA) in sepals and petals is significantly higher than in leaves. To understand whether the high levels of stress responsive transcripts and the higher SA content affect defense, wild-type plants (Col-0) and transgenic plants defective in SA accumulation (nahG) were challenged with the biotrophic fungus Golovinomyces cichoracearum, the causal agent of powdery mildew, and the necrotrophic fungus Botrytis cinerea. NahG leaves were more sensitive than those of Col-0, suggesting that in leaves SA has a role in the defense against biotrophs. In contrast, sepals and petals of both genotypes were resistant to G. cichoracearum, indicating that in the flower, resistance to the biotrophic pathogen is not critically dependent on SA, but likely dependent on the up-regulation of stress-responsive genes. Since sepals and petals of both genotypes are equally susceptible to B. cinerea, we conclude that neither stress-response genes nor increased SA accumulation offers protection against the necrotrophic pathogen. These results are interpreted in the light of the distinctive role of the flower and we propose, that in the early stages, the sepal may act as a chemical defense barrier of the developing reproductive structures against biotrophic pathogens.